2022
DOI: 10.1016/j.apnu.2021.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Mediating the effects of depression in the relationship between university students' attitude toward suicide, frustrated interpersonal needs, and non-suicidal self-injury during the COVID-19 pandemic

Abstract: Kang, et al., Mediating the effects of depression in the relationship between university students' attitude toward suicide, frustrated interpersonal needs, and non-suicidal self-injury during the COVID-19 pandemic, Archives of Psychiatric Nursing (2021),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
(54 reference statements)
0
4
0
2
Order By: Relevance
“…Additionally, depression contributed to the largest total effect on impulsivity and suicidal orientation. These findings are consistent with what has been reported in other research that has shown that the frustrated psychological needs present in young people with hopelessness and depression put them at greater risk of developing beliefs oriented toward suicide (Park et al, 2022;Shin & Choi, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, depression contributed to the largest total effect on impulsivity and suicidal orientation. These findings are consistent with what has been reported in other research that has shown that the frustrated psychological needs present in young people with hopelessness and depression put them at greater risk of developing beliefs oriented toward suicide (Park et al, 2022;Shin & Choi, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the second peak of NSSI occurs in young adulthood, that is, around the age of 20 to 24, which, for many people, accords with college years [13]. For many people, going to college is a turning point in the transition from adolescence to adulthood [14]. Although this period tends to be surprising and exciting, there is often significant instability in terms of employment, housing, finances, and relationships [15].…”
Section: Introductionmentioning
confidence: 99%
“…La frustración denotaría un fracaso en las relaciones interpersonales que genera una carga de aislamiento social debido a la desconexión entre individuos. Los instantes donde no hay conexiones significativas podrían afectar el estado de ánimo, influyendo en la depresión y teniendo un impacto en las conductas suicidas 22 .…”
Section: Discussionunclassified